Stratifikasi Sosial dan Mobilitas Vertikal melalui Pendidikan Islam: Studi tentang Peran Madrasah dalam Transformasi Status Sosial Ekonomi Masyarakat - Jumawati Jumawati; Muhammad Nur Maallah; Irma Irma; Muhammad Afit Imran; Rapia Kahri (Journal of Humanities, Social Sciences, and Education, 2025)
Islamic education plays a strategic role in creating vertical mobility and reducing social inequality through equal access and learning opportunities. Madrasahs, as Islamic educational institutions, function not only as institutions for religious learning but also as agents of socio-economic change in society. This literature review aims to examine the relationship between social stratification and vertical mobility in the context of Islamic education, specifically the role of madrasahs in improving the socio-economic status of the community. The research method used is a literature review, reviewing empirical and theoretical research findings from various recent sources (2019–2024). The results indicate that madrasahs play a significant role in creating social mobility by improving students' religious, academic, and entrepreneurial skills. Furthermore, madrasahs are able to bridge the social gap between lower and middle economic groups through inclusive education policies. In the modern context, digital transformation and government policies regarding madrasahs have strengthened their position as instruments of human development and social mobility. Thus, Islamic education through madrasahs contributes significantly to changing social structures towards a more just and productive society.